The Role of Job Satisfaction as Intervening Variable in the Relationship Between Career Development, Work-Life Balance and Turnover Intention in Outsource Solution Company - Ratnawita Ratnawita; Hartanto; Helmi Ali; Akhmad Baidun; Laila Qadriyani MR (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
With job satisfaction acting as a moderating factor for employees, this study aims to demonstrate how work-life balance and career development factors affect turnover intention. The IBM SPSS v26 software program and the path analysis approach were employed in this study's data analysis technique. A validity test, a reliability test, a normalcy test, a coefficient of determination test, a F test, a t test, and a Sobel test are all employed in the analysis to identify the mediating impact in this study. The study's findings demonstrate that: work-life balance has no effect on job satisfaction; career development influences job satisfaction; work-life balance and career development both affect job satisfaction; work-life balance has no effect on turnover intention; career development influences turnover intention; job satisfaction affects turnover intention; and work-life balance simultaneously affects turnover intention.